Stress Among Patients During Hospitalization: A Study from Central India - Neeraj Chhari; Satish C Mehta (Medsci Publications, 2016)
Background: The process of hospitalization is a very traumatic experience whether it's a male or a female. People have to move their life setting from the familiar to unfamiliar environment, loosing their privacy, and sense of security and individuality. There are several factors which can lead to stress and recovery of the patients. This study was undertaken to know the factors or predictors which can lead to stress in hospitalized patients. Objectives: To measure stress and factors associated with stress during hospitalization. Methods: Observational cross sectional study was carried out by indepth interview  using pre tested structured proforma on patients admitted to the medicine,OBG,Surgery and Orthopaedic wards and rated on 11 point Thurstone scale. Result: Total 700 patients participated,out of which,510(72.9%) were under stress due to hospitalization. Females (76.5%) and patients from urban (77.6%) area were in more stress.Fear of loosing body part or function,stress of undergoing operation and not knowing the outcome of treatment were found to be major factors for stress. Conclusion: The strangeness of the hospital environment can act as a potential source of stress. A warm welcoming attitude at admission on the part of nurse and members of the health team contribute significantly to minimizing the trauma of hospital stay.